Criticism in the Romantic Relationships of Individuals With Social Anxiety. Issue 4 (July 2017) - Porter, Eliora; Chambless, Dianne L.; Keefe, John R.
Abstract: Social anxiety is associated with difficulties in intimate relationships. Because fear of negative evaluation is a cardinal feature of social anxiety disorder, perceived criticism and upset due to criticism from partners may play a significant role in socially anxious individuals' intimate relationships. In the present study, we examine associations between social anxiety and perceived, observed, and expressed criticism in interactions with romantic partners. In Study 1, we collected self-report data from 343 undergraduates and their romantic partners on social anxiety symptoms, perceived and expressed criticism, and upset due to criticism. One year later couples reported whether they were still in this relationship. Results showed that social anxiety was associated with being more critical of one's partner, and among women, being more upset by criticism from a partner. Social anxiety was not related to perceived criticism, nor did criticism variables predict relationship status at Time 2. In Study 2, undergraduate couples with a partner high ( n = 26) or low ( n = 26) in social anxiety completed a 10-minute, video-recorded problem-solving task. Both partners rated their perceived and expressed criticism and upset due to criticism following the interaction, and observers coded interactions for criticism. Results indicated that social anxiety was not significantly related to any of the criticism variables, but post hoc analyses cast doubts upon the external validity of the problem-solving task. Results are discussed in light of known difficulties with intimacy among individuals with social anxiety. Highlights: Social anxiety was not associated with perceived criticism from romantic partners. Among women, social anxiety was associated with becoming more upset by criticism. Social anxiety was associated with being more critical of one's partner. Neither criticism nor its interaction with social anxiety predicted break-up.